2021
DOI: 10.37992/2021.1203.126
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability and association analysis in rice (Oryza sativa L.) germplasm based on biometrical and floral traits

Abstract: The present experiment was carried out to evaluate 150 rice germplasm accessions for biometrical and floral traits to assess the amount of variability and association among them. Eight biometrical and thirteen floral characters were recorded. Analysis of variance showed that there was a significant variation observed for all the characters studied at a 5% probability level. High PCV and GCV was recorded for spikelet sterility percentage (28.78 %, 21.61 %), number of pollen grains per anther (22.25 %, 21.08 %) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 3 publications
5
1
0
Order By: Relevance
“…High PCV and GCV values and high genetic advances were recorded for these traits, suggesting further improvement of lines for these characteristics for further selection and subsequent use in the breeding program. Similar results were also reported by [ 54 , 55 , 56 , 57 , 58 , 61 , 63 ]. In general, heritability along with genetic advances can be useful in the selection program.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…High PCV and GCV values and high genetic advances were recorded for these traits, suggesting further improvement of lines for these characteristics for further selection and subsequent use in the breeding program. Similar results were also reported by [ 54 , 55 , 56 , 57 , 58 , 61 , 63 ]. In general, heritability along with genetic advances can be useful in the selection program.…”
Section: Discussionsupporting
confidence: 92%
“…Analysis of variance showed highly significant differences between all genotypes for all the studied traits ( Table 2 ), which indicates that each genotype is genetically different from the other for yield, its components, floral traits, and grain quality, indicating that there is variability among the studied lines and they would respond positively to selection. The set of genotypes used in the current study indicated that there were statistically significant differences between them among all the traits that were studied, and these results were consistent with the findings of [ 54 , 55 , 56 , 57 , 58 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Thus, phenotypic selection might be beneficial in the improvement of traits under consideration. Days to maturity recorded the lowest PCV and GCV illustrating that there was meagre variation in these parameters and the results were in concordance with Aswin et al (2021) and Emi et al (2021). Moderate PCV and GCV were noticed for the plant height and length of the panicle similar to the findings of Bhargava et al (2021) and Prasannakumari et al (2020); grain L/B ratio in corroboration with the results of Roy et al (2021) and Aswin et al (2021) and for grain length reported by Priyanka and Gauraha (2020).…”
Section: Resultssupporting
confidence: 85%